(untitled) (Indian Journal of Animal Production and Management, 2025)
Majority of the Indian economy is in the hands of small and marginal farmers with 80% of total land holdings having less than 1ha of cultivable land. Integration of livestock with crop provides scope for effective utilization of byproducts which assures the profitability of the farming system. Integrated Farming System approach is required to enhance the living standards of the small and marginal farmers. The present study revealed the profitable farming systems in major farming situations and its diversification. It was observed that the farming system consisting of seasonal crops along with dairy, sheep and poultry was found most profitable than cultivation of crops alone. The economic sustainability of the faming systems was evolved through Sustainability Value Index (SVI). Most of the farming systems in the rainfed black soils were found sustainable. But only one farming system in rainfed red soils was found sustainable.The Simpson Index of Diversification (SID) was also assessed and observed more diversification in the farming systems under rainfed red soils. The results of the study are useful for small and marginal farmers to adopt the suitable farming system.